Risk Analysis of Costs and Income of Clove Farming in Balassuka Village, Tombolopao Subdistrict, Gowa District - Ramadhani, Putri Amalia; Amruddin; Saleh, Muh Ikmal (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study aims to determine the amount of production costs and income as well as the risk of costs and income of clove farming. This research was conducted in Balassuka Village, Tombolopao District, Gowa Regency for 2 months, namely in September - October 2024. This research method uses purposive sampling, which is a deliberate sample selection technique by taking 30 clove farmers in Balassuka Village, Tombolopao District, Gowa Regency. Data analysis techniques used are production cost analysis, revenue analysis, income analysis and coefficient of variation (CV) analysis.The results showed that: (1) Production costs that have been incurred by clove farmers during one harvest season amounted to Rp.209,993,332 with an average production cost of Rp.6,999,778, while the income earned by clove farmers amounted to Rp.835,806,668 / year with an average income earned by clove farmers is Rp. 27,860,222. (2) The risks faced by farmers in clove farming are cost risk and income risk. The Coefficient of Variation (CV) of the cost risk is obtained at 0.08 (0.08 < 1) while the Coefficient of Variation (CV) of the income risk is 0.05 (0.05 < 1). Then the results of these calculations indicate that the cost and income risks in clove farming borne by farmers are relatively low.